Pengaruh Kuat Arus Dan Besar Sudut Kampuh Terhadap Kekuatan Impact Dan Nilai Kekerasan Plat Baja Karbon Rendah Dengan Menggunakan Las SMAW - Soleh Abdul Aziz (Universitas Negeri Malang, 2020)
Abstract: Welding is welding that utilizes flame heat in electric arcs to melt electrodes and workpieces. SMAW welding is widely used because of its relatively easy to use, cost-friendly and maximum quality results. In conducting welding has several factors that will affect the quality of the welding results such as a welder, welding current and metal distance and welding seam angle. This study aims to determine whether there is an influence of current variations and magnitude of the seam angle to the value of the impact strength and the hardness value of the SMAW welding results. This study uses a pre-experimental method with a one-shot case model. The results of this study indicate the highest impact strength values of current variations in the 80 Ampere specimen at the angle of seam V 60o in the amount of 0.0799 J / mm2 and in the 80 Ampere specimen in the angle of the 80o V in the seam angle of 0.0942 J / mm2. Then for the highest impact strength value variation of seam angle V group of seam angle specimen V 80o current 80 Amperes is equal to 0.0942 J / mm2 and specimen angle of seam V 80o current 100 Ampere 0.0824 J / mm2. The highest hardness value is obtained with a variation of the current specimen group of 100 Ampere in the angle of seam V 60o that is equal to 187.1 HVN and in the specimen group 100 Ampere with the angle of contact V 80o that is equal to 204.4 HVN. Then the highest hardness value variation angle seam V specimen V 80o with current 80 Amperes is equal to 191.63 HVN and specimen angle of seam V 80o with 100 amperes current that is equal to 204.4 HVN. KeyWords : SMAW, Welding current, V groove, Impact Strength, Hardness